Bowel habits of exclusively breastfed 0-4 month-old babies - Edi S Tehuteru; Agus Firmansyah; Bambang Madiyono (Indonesian Pediatric Society Publishing House, 2016)
Background Exclusively breastfed newborns have frequent bowel movements and sometimes watery stool, which parents or doctors might think as diarrhea. Objective The aim of this study was to observe the bowel habits of exclusively breastfed infants. Methods A longitudinal study was done on 100 babies born be- tween November and December 2002 in Cinta Kasih Maternity Hospital. The inclusion criteria were fullterm baby, exclusively breastfed for 4 months, and informed consent from parents. Ba- bies with problems in organ or nerve that influenced the gastrointes- tinal tract were excluded. Stool frequency, consistency, and color were observed. Results The mean stool frequency per day were 3 times in the 1 st week (95%CI 2.6;3.4), 2 times in the 2 nd week (95%CI 1.7;2.3), 1.8 times in the 3 rd week (95%CI 1.5;2.1), and 1.5 times in the 4 th week (95%CI 1.3;1.7). In the second and third month, it was 1.4 times a day and the fourth month, 1.2 times a day. The consis- tency of meconium was soft in the first four days. After that, 18% of babies had watery stool, which increased to 30% on day 15-113. In the last week of the fourth month, all babies had soft stool. Meco- nium was black and lasted for 1-3 days. On the fourth day, the stool became yellow. On day 5-14, 6% of babies had green stool, which increased to 12% on day 15-120. Conclusion The first week of the first month was the week when the stool frequency was highest compared to the weeks or months after. The consistency of meconium was soft. After it disappeared, most babies had soft stool. Eighteen up to 30% percent of babies had watery stool. Regarding the color, meconium was black and stayed for 1-3 days. After that, most babies had yellow stool and 6- 12% had green stool